Restorative Justice of Corruption in the Villages: Array - Adhayanto, Oksep (Acta Universitatis Danubius. Juridica, 2020)
The development of village government since the jokowi period increased dramatically. The budget allocation in the form of village funds and allocation of village funds is so large that the village government can carry out development well. The amount of budget obtained by the village government also brings a bad side to the village apparatus, such as the number of village apparatuses that stumble over corruption cases. Concrete steps need to be sought in an effort to have an effect on corruption in the village. This paper attempts to look at other approaches besides law enforcement to crack down on perpetrators of corruption in the village. research results show that the cause of the emergence of corruption is due to convoluted administration and lack of human resource capacity. With this consideration, the law enforcement approach to taking action against corruptors in the village needs to be reconsidered. The approach of coaching and mentoring for village heads and village officials is important rather than merely giving the effect of imprisonment to the perpetrators.